Analysis of the Preparedness of the Yogyakarta Search and Rescue Office in Responding to Accidents in the Waters of Parangtritis Beach - Giyong Widianto; Erni Saharuddin (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to analyze the level of preparedness of the Yogyakarta Search and Rescue Office in responding to accidents in the waters of Parangtritis Beach, Bantul Regency. Using a qualitative descriptive approach, data were obtained through interviews, observations, and documentation of SAR personnel and the surrounding community. The results indicate that the Yogyakarta Search and Rescue Office has a good level of preparedness, indicated by the availability of rotating standby officers, the readiness of facilities and infrastructure, and the implementation of special alerts. However, challenges remain, particularly in terms of the limited number of personnel to handle large-scale incidents, low public awareness, and the lack of early detection tools. The weaknesses of this study lie in its limited scope, which focuses only on Parangtritis Beach, so the results cannot be generalized to other coastal areas. Furthermore, it is recommended that further research conduct comparative studies in various vulnerable coastal tourist areas, integrate IoT-based early warning technology analysis, and expand local community participation to obtain a more comprehensive picture of preparedness. Collaborative efforts between agencies and increased public education remain important factors in increasing the effectiveness of responses to accidents in the waters. Keywords : Preparedness; Search and Rescue; Parangtritis Beach; Marine Accidents;